Penegakan Hukum terhadap Peredaran Rokok Ilegal Melalui Kantor Bea Cukai Medan - Kamaludin Kamaludin; Mhd Yadi Harahap (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Indonesia is a developing country. as a developing country, Indonesia takes advantage of state revenue from Customs and Excise. Customs and Excise is held responsible by the Directorate General of Customs. One of the things he is responsible for is cigarettes. Even though the cigarette customs and excise authority has been held, The legal permits marked still not acquired by the cigarette companies with excise stamps by customs in the city of Medan, which these companies have committed violations. This study aims to examine how cigarettes are regulated in the city of Medan where there are no excise stamps, As well as law enforcement actions against traffickers of illicit cigarettes in the city of Medan who do not utilize excise stamps, do so with used excise stamps, do so with false excise stamps, or both. In this study, the normative legal research methodology was used. A conceptual approach is the method used. Interviews were employed in this research as a lawful material collecting method. Primary, secondary, and tertiary data were employed in this investigation. The gathered data is subsequently subjected to a methodical analysis. This investigation discovered that cigarettes produced from chopped tobacco and rolled with paper are those that are sold without excise stamps and are classified as illicit cigarettes, as stated in Law Number 39 of 2007 about modifications to Law Number 11 of 1995 concerning Excise. article 4 paragraph letter (c). Keyword: Customs; Ilegal; Circulation of Cigarettes.